AI and its consequences for the written word - Hellström, Thomas (Frontiers in Artificial Intelligence, 2024)
The latest developments of chatbots driven by Large Language Models (LLMs), more specifically ChatGPT, have shaken the foundations of how text is created, and may drastically reduce and change the need, ability, and valuation of human writing. Furthermore, our trust in the written word is likely to decrease, as an increasing proportion of all written text will be AI-generatedand potentially incorrect. In this essay, I discuss these implications and possible scenarios for us humans, and for AI itself.